Value Chain Analysis Towards Sustainability: A Case Study of Fishery Business in Kota Kupang, Indonesia - Kabu, Enos; Tira, Deviarbi Sakke (International Journal of Economics and Financial Issues, 2015)
This study aims to provide a value chain map as well as its analysis over fishery business in Kota Kupang, Indonesia. Actors of this business were mapped using the value chain approach then analysed further using profitability ratios in order to know how much profit gained by each actors within the value chain and its impacts towards sustainability of fishery business. In-depth interview and focused group discussion were conducted with 25 supply chain members covering fishermen, association of fishermen members, middlemen, traders, exporters, Fishery Deparment of Local Govenrment, Investment Body, Transporters and Consumers located in Kota Kupang. Data collected were analysed using financial ratios then ended by providing a value chain map complete with its description. This study shows that exporters and big local traders gained higher profits compared to fishermen and other actors within the value chain. Also, there is a big business circle created and managed by those who have capital under the cooperation of andon fishermen, local people, and financing companies. To better addressed the sustainability issue of fishery business in Kota Kupang, it is therefore recommended that the local and central government should hand in hand with local fishermen and local fishery business actors, including local fishermen association to provide improvement of fishery related regulations for local people quality of life and economic growth of Kota Kupang, Indonesia. Keywords: Value Chain, Fishery Sector; Profitability; Sustainability. JEL Classifications: M00